Patriotic and Pious Muslim Intellectuals in Twentieth-Century China: The Case of Ma Jian (American Journal of Islam and Society, 2006)
The fall of the Qing dynasty (1644-1911) and the founding of the modern Chinese nation-state brought both opportunities and challenges to Chinese Muslims. No longer having to deal with emperorship and its foundational ideology, Confucianism, they were soon confronted with new state ideological impositions, namely, Han nationalism and socialism, imposed by the Republican and Communist regimes. These new challenges were both threatening and promising, for although the new ideologies were fundamentally antithetic to Islam, the new regimes promised an equal status to Chinese Muslims and saw how they could aid national diplomacy and international relations with Muslim countries. Within this context, China’s Muslim intellectuals tried to reorient and reposition Muslims and Islam by minimizing differences and maximizing commonalities during both the Republican and the Communist regimes. By studying Ma Jian (1906-78), one of modern China’s most influential and representative Muslim intellectuals, as well as his juxtaposition of Islam and China, I look at the way of being a modern Chinese Muslim intellectual in China’s post-1949 internal and international contexts. The Turkic Muslim communities in Xinjiang and elsewhere in China are excluded from this study.